Rare presentation of SMARCA4-deficient thoracic tumor diagnosed with palatal tonsil biopsy - Naomi Kudo; Akira Kurose; Ryutaro Hara; Junko Takahata; Kengo Hasui; Atsushi Sato; Atsushi Matsubara (Elsevier, 2021)
SMARCA4-deficient thoracic tumor (SMARCA4-DTT) is a relatively new pathological entity with highly aggressive characteristics. With mass lesions developing in the thoracic region, patients tend to complain of chest symptoms, such as dyspnea or chest pain. Here, we encountered a rare case of SMARCA4-DTT presenting to the otolaryngology clinic with painful throat and diagnosed by palatal tonsil biopsy.A 47-year-old male patient with heavy smoking habit presented to a nearby clinic due to sore throat occurring a few days before presentation. Antibiotic therapy was prescribed for the treatment of acute tonsillitis. However, the pain exacerbated, and mass lesion in the submandibular region started to develop. The patient was referred to our department for detailed examination due to suspected pharyngeal malignancy. Right tonsil biopsy was performed, and the patient was diagnosed with SMARCA4-deficient tumor. Computed tomography illustrated compressive mass lesion in the mediastinum and multiple swelling of systemic lymph nodes. Although radiotherapy and chemotherapy were performed, the lesion rapidly progressed, and brain metastasis also occurred. The patient followed a poor disease course and died 91 days after the first symptom.SMARCA4-deficient tumor has been reported in other sites, such as ovary, uterus, and gastrointestinal tract. The purpose of the present article is to make literature review on clinicopathological characteristics of SMARCA4-deficient tumors in various sites while reporting the rare presentation of SMARCA4-DTT.